Epicanthus correction with a modified asymmetric Z-plasty. (September 2022) - Li, Gaofeng; Fu, Anqi; Zhang, Bo; Ding, Wei; Ouyang, Huawei; Xu, Suqi; Long, Xiren; Liu, Xiaojia
Summary: The study aimed to explore the clinical efficacy of the modified asymmetric Z-plasty with a central axis from the point near the edge of the skin fold of the medial canthus to the point of the innermost palpebral edge of medial canthus for epicanthus correction. A total of 130 followed-up patients who received modified asymmetric Z-plasty for epicanthus correction in Hunan Provincial People's Hospital from January 2019 to December 2019 were included. All patients were followed up with at 1, 3, and 6 months after surgery, and the scarring and surgical outcomes were assessed. The results showed the surgical wounds were healing well, and the sutures were removed at 7 days postoperatively in all patients. At 6 months postoperatively, epicanthus correction was successful in all patients, the lacrimal caruncle was moderately exposed, the incision was not red, and there were no obvious prominent scars. Slightly prominent and uneven scars below the edge of the lower eyelid were observed in 3 patients. Among these 3 patients, 1 patient received no further treatment, and the outcomes were considered acceptable; the outcomes were improved in the remaining 2 patients after a single session of fractional laser treatment, and none of these patients received further surgery. In conclusion, t he modified asymmetric Z-plasty with a central axis from the point near the edge of the skin fold of the medial canthus to the point of the innermost palpebral edge of medial canthus is relatively simple and provides good surgical results for epicanthus correction.